Strong histamine torsion Raman spectrum enables direct, rapid, and ultrasensitive detection of allergic diseases - Haogang Zhu (Elsevier, 2021)
Summary: Allergic diseases are closely related to degranulation and release of histamine and difficult to diagnose because non-allergic diseases also exhibit the same clinical symptoms as allergy. Here, we report direct, rapid, and ultrasensitive detection of histamine using low-frequency molecular torsion Raman spectroscopy. We show that the low-frequency (<200 cm−1) Raman spectral intensities are stronger by one order of magnitude than those of the high-frequency Raman ones. Density functional theory calculation and nuclear magnetic resonance spectroscopy identify the strong spectral feature to be from torsions of carbon-carbon single bonds, which produce large variations of the polarizability densities in the imidazole ring and ethyl amino side chain. Using an omniphobic substrate and surface plasmonic effect of Au@SiO2 nanoparticles, the detection limit (signal-noise ratio >3) of histamine reaches 10−8 g/L in water and 10−6 g/L in serum. This scheme thus opens new lines of inquiry regarding the clinical diagnosis of allergic diseases.